Islamic Values in the Malem Tradition of Selikuran Tirto Village, Grabag District, Magelang District - Erkham Maskuri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Malem Selikuran tradition is a tradition that takes place on the night of the 21st of Ramadan. The Malem Selikuran tradition is carried out to commemorate the death of Sunan Geseng. Malem Selikuran is unique because this tradition is followed by Muslim communities in the Tirto area and outside the region during the month of Ramadan. This study aims to describe the emergence of Selikuran culture in Tirto village, Grabag sub-district, Magelang district and to find out Islamic values ​​in the Malem Selikuran tradition. This research uses the field method (field research) with a descriptive approach. The data were obtained from direct observations and interviews with Tirto villagers. The results of this study are in the form of Islamic values ​​contained in the Malem Selikuran tradition, including religious values, historical values ​​and moral values